The association between non-alcoholic fatty liver disease and urinary incontinence among adult females in the United States - Xinyuan Li; Weiwei Zhou; Guangsheng Hu (BMC Public Health, 2024)
Abstract Background and objectives Non-alcoholic fatty liver disease (NAFLD) and urinary incontinence (UI) are both highly prevalent and age-related diseases. Nevertheless, the link between NAFLD and UI is unclear. Hence, the study was designed to evaluate the association between the NAFLD and UI (including UI types) in a nationally representative sample of United States (US) female adults. Methods We conducted this study used data from U.S. female adults in the National Health and Nutrition Examination Survey (NHANES) 2017-March 2020 (pre-pandemic) cycles. The diagnosis of NAFLD is based on Vibration controlled transient elastography (VCTE) and absence of know liver diseases and significant alcohol consumption. The diagnosis and types of UI were assessment using a self-report questionnaire. Multivariable logistic regression models were used to analyze the association between NALFD and UI. Stratified analyses based on age, obesity, race, educational level, married status, PIR, and smoking status were conducted. Results Of the 2149 participants, the mean (95% CI) age was 53.9 (52.7–55.0), 686 (61.1%) were Non-Hispanic White. UI was significantly more common in participants with NAFLD [490 (64.7%)] than those without NAFLD [552 (44.9%)]. Adjusted for age, race/ethnicity, marital status, educational level, family poverty income ratio (PIR) status, alanine aminotransferase (ALT), aspartate aminotransferase (AST), smoking status, obesity, type 2 diabetes mellitus (T2DM), hypertension and insulin resistance (IR) in a multivariable logistic regression model, NALFD were associated with UI [OR: 1.93, 95%CI 1.23–3.02, P = 0.01] and urge UI [OR: 1.55, 95%CI 1.03–2.33, P = 0.03], while patients with NAFLD did not show an increased odds in stress UI and mixed UI when compared with those without NAFLD subject (P > 0.05). In the subgroup analyses, NAFLD remained significantly associated with UI, particularly among those participants without obesity (OR: 2.69, 95% CI 1.84-4.00) and aged ≥ 60 years (OR: 2.20, 95% CI 1.38–3.51). Conclusions Among US female adults, NAFLD has a strong positive correlation with UI. Given that NAFLD is a modifiable disease, these results may help clinicians to target female patients with NAFLD for treatments and interventions that may help prevent the occurrence of UI and reduce the symptoms of UI.